Evaluation of pigtail macaques as a model for the effects of copper intrauterine devices on HIV infection. Issue 5 (27th December 2013) - Engel, Robyn M.; Morris, Monica; Henning, Tara; Ritter, Jana M.; Jones, Tara L.; Dietz, Sharon; Ayers, Jessica; Vishwanathan, Sundaram A.; Jenkins, Leecresia; Zaki, Sherif; Wildemeersch, Dirk; Garber, David; et al.
Abstract Background Long‐acting, hormonal contraception may increase HIV risk. Copper intrauterine devices (IUDs) could serve as non‐hormonal alternatives. We pilot a pigtail macaque model for evaluating HIV susceptibility factors during copper IUD use. Methods Frameless and flexible GyneFix® copper IUDs were surgically implanted into three SHIVSF162p3‐positive macaques via hysterotomy and monitored for up to 4 months. Four macaques served as non‐IUD controls. Results All animals retained the devices without complications. No consistent change in vaginal viral RNA or inflammatory cytokines was seen. Two animals had altered menstrual cycles and experienced marked thinning of vaginal epithelium after IUD insertion. Histological examination of uterine tissue at necropsy revealed endometrial ulceration and lymphocytic inflammation with glandular loss at sites of direct IUD contact. Conclusions Although the need for insertion surgery could limit its usefulness, this model will allow studies on copper IUDs and SHIV shedding, disease progression, and HIV susceptibility factors.